(3GdaJM GdQHGfi aj Md CdaGX JUQja GdRfLGfis - (3TeS GdOjf eMeO GdTQHjfj GdNWjHs; (3GdRfLGfj , YHO GdhgGH Hf EHQGgje Hf YHO GdhgGH GdNRQLj, YRGdOjf CHh GdaVGFd,J (B655 (3g` s ((3SYO GdOjf GdLYHQj GdQaGYi GdNdjd GdTGaYi s)
(3ChdgG (B:s
(3hHYO ajbhd abjQ GdNWjH deG QCjJ eNJUQ GdJUQja GdPi UfYg GdEeGe GdRfLGfi s
(3BNQgG (B:s
(3Ch ZjQgeG ddfhY hcPG GdHhGbi hGddg SHMGfg hJYGdi CYde s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdUQas